Design Mockup of the Teacher Attendance Monitoring Information System at SMK Ibnu Sina Batam: Desain Mockup Sistem Informasi Pemantauan Kehadiran Guru di SMK Ibnu Sina Batam - Arifin, Nofri Yudi (YCMM, 2024)
Teacher attendance is a crucial aspect in maintaining the quality of education in schools. SMK Ibnu Sina Batam currently employs a manual method for recording teacher attendance, which is prone to errors, delays in data compilation, and a lack of transparency in reporting. This study aims to develop a web-based information system mock-up to monitor teacher attendance more efficiently, accurately, and transparently.The research adopts the prototype model, which allows system development by involving users in each stage. The designed mock-up includes key features such as user login, attendance recording, teacher data management, and attendance report generation. The analysis results indicate that a web-based system offers advantages over the manual method in terms of recording speed, data security, and information accessibility.The findings suggest that a web-based teacher attendance monitoring system can serve as an effective solution to enhance school administration efficiency. Further implementation is recommended by incorporating biometric features and a mobile version to improve system functionality.